2021
DOI: 10.3389/fnmol.2020.611179
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Spinal ASIC1 and NKCC1 Expression Contributes to Chronic Visceral Pain in Rats

Abstract: Aims: To determine whether acid-sensing ion channel 1 (ASIC1)–sodium-potassium-chloride cotransporter 1 (NKCC1) signaling pathway participates in chronic visceral pain of adult rats with neonatal maternal deprivation (NMD).Methods: Chronic visceral pain was detected by colorectal distension (CRD). Western blotting and Immunofluorescence were performed to detect the expression and location of ASIC1 and NKCC1. Whole-cell patch-clamp recordings were performed to record spinal synaptic transmission.Results: The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Chronic visceral pain was induced by neonatal maternal deprivation (NMD), as previously described. 8 , 27 In brief, from day 2 to day 15 after birth, the newborn C57BL/6 male mouse pups of the NMD group were placed in a separate box with an electric blanket for 3 hours. After the separation period, the pups were placed back in their dams.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic visceral pain was induced by neonatal maternal deprivation (NMD), as previously described. 8 , 27 In brief, from day 2 to day 15 after birth, the newborn C57BL/6 male mouse pups of the NMD group were placed in a separate box with an electric blanket for 3 hours. After the separation period, the pups were placed back in their dams.…”
Section: Methodsmentioning
confidence: 99%
“… 5 Neonatal maternal deprivation (NMD) is a typical early life stress that has been shown to induce visceral pain behavior. 18 , 27 At present, most research studies on visceral pain have focused on the investigation of the molecular events underlying the peripheral nervous system and the spinal cord. 29 , 41 , 47 However, the studies that have focused on the brain are very limited, and the role of the brain in regulating visceral pain remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The acid-sensing ion channel (ASIC) family consists of six subtypes (ASIC1a, 1b, 2a, 2b, 3, and 4) encoded by four genes ( Hamann et al, 2015 ; Zhu et al, 2022 ). ASIC1a has been frequently studied because of its abundant levels in the mammalian central nervous system ( Wemmie et al, 2003 ; Li et al, 2020 ). In addition, ASIC1a is present in areas of brain regions that are important in the pain process, including the ACC and hippocampus, as well as the amygdala ( Alvarez de la Rosa et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this circuit-level segregation, a selective loss of cutaneous affective pain may not be detected via assays that only measure first-line reflexive-defensive reactions (Ma, 2022; Mogil, 2020). Meanwhile, despite great clinical relevance and unmet medical need, modern genetic and viral tools have rarely been used to characterize spinal circuits transmitting visceral sensory information, even though electrophysiological, molecular and behavioral studies have revealed sensitization in spinal neurons following visceral inflammation or stress (Defaye et al, 2022; Farrell et al, 2017; Gamboa-Esteves et al, 2004; Harrington et al, 2012; Honore et al, 2002; Lai et al, 2011; Li et al, 2020; Long et al, 2022; Nishida et al, 2022; Traub, 2000; Wang et al, 2005; Wu et al, 2022; Zhang et al, 2013). As such, it is still poorly understood how nociceptive and affective dimensions of visceral sensory information are transmitted through the spinal cord.…”
Section: Introductionmentioning
confidence: 99%